2021
DOI: 10.3390/cancers13225807
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Wavelength Fluorescence Monitoring of Photodynamic Therapy: From Analytical Models to Clinical Studies

Abstract: Fluorescence imaging modalities are currently a routine tool for the assessment of marker distribution within biological tissues, including monitoring of fluorescent photosensitizers (PSs) in photodynamic therapy (PDT). Conventional fluorescence imaging techniques provide en-face two-dimensional images, while depth-resolved techniques require complicated tomographic modalities. In this paper, we report on a cost-effective approach for the estimation of fluorophore localization depth based on dual-wavelength pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The authors in [48] demonstrated the effectiveness of dual-wavelength ALA-PDT dosimetry of patients with actinic keratosis (n = 15) using PpIX photobleaching with fluorescence excitation at 405 and 639 nm, which makes it possible to take into account the PS distribution in the superficial and deeper layers of biological tissues. Previously, the effectiveness of two-wave Ce6-PDT monitoring for changes in the PS fluorescence intensity at different depths of biological tissue was also demonstrated and the results were shown to correspond to the results of Monte Carlo simulation [124]. Currently, preliminary numerical modeling methods are also being introduced into clinical practice to predict optimal PDT energy doses.…”
Section: Discussionmentioning
confidence: 85%
“…The authors in [48] demonstrated the effectiveness of dual-wavelength ALA-PDT dosimetry of patients with actinic keratosis (n = 15) using PpIX photobleaching with fluorescence excitation at 405 and 639 nm, which makes it possible to take into account the PS distribution in the superficial and deeper layers of biological tissues. Previously, the effectiveness of two-wave Ce6-PDT monitoring for changes in the PS fluorescence intensity at different depths of biological tissue was also demonstrated and the results were shown to correspond to the results of Monte Carlo simulation [124]. Currently, preliminary numerical modeling methods are also being introduced into clinical practice to predict optimal PDT energy doses.…”
Section: Discussionmentioning
confidence: 85%
“…Another factor that may affect the performance of PDT in deeper tissue layers is the penetration depth of irradiation, which is used to activate the accumulated PS. In this study, with the chlorin-based PS, we compare the effect of PDT performance at the wavelengths of 660 and 405 nm, both of which correspond to chlorin e6 absorption peaks [ 24 ] and were proposed for PDT performance [ 26 ]. Since the absorbed light dose distribution within tissue cannot be measured directly, we performed Monte Carlo simulations of the absorbed dose distribution for the values of optical properties typical for tumors and muscular tissues summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Topically applied PSs do not require intravenous injection, and they benefit from a simple application procedure [ 23 ]. Chlorin-based photosensitizers feature two peaks in their absorption spectrum in the red and blue bands, thus providing different penetration depths owing to significant differences in the biotissue optical properties of these bands [ 24 , 25 ]. Previously, PDT with topically applied PS has demonstrated limited efficiency in tumor treatment, owing to the limited penetration of PS into the tumor [ 26 ]; however, its application to the tumor bed after the procedure seems to be promising.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Monte Carlo (MC) technique for light transport studies is based on modeling of a large number of random photon trajectories in turbid media with following statistical analysis of the collected data [32]. In this work previously developed platform for threedimensional MC modeling of light propagation in biological tissues [22,33,34] was customized by implementing elongated absorbers mimicking different vessels filled with blood within biotissue. It was employed for the generation of the maps of the absorbed light dose distribution at probing wavelength λex 𝐻(𝑥, 𝑦, 𝑧, λ 𝑒𝑥 ) in a flat tissue-like homogenous medium containing cylinders mimicking blood vessels of different diameters, embedding depths and orientations corresponding to typical morphological parameters.…”
Section: Monte Carlo Modelingmentioning
confidence: 99%